Application of Calcium-Based Nanomaterials in Art Sculpture Reinforcement Technology - Kun Di (International Journal of Analytical Chemistry)
In order to solve the problem of the reinforcement effect of art sculpture, the author proposes the application of a calcium-based nanomaterial in the reinforcement process of art sculpture. This application mainly passes the unconfined compression test, direct shear test, penetration resistance test, and disintegration test, and an in-depth evaluation of the reinforcement effect of different calcium-based reinforcement agents on the site soil was carried out from the perspective of mechanical strength and water stability. The results showed the following: Compared with the untreated samples, the unconfined compressive strength of the samples treated with nano-calcium oxide and nano-calcium hydroxide increased by 13.5% and 25.9%, respectively, and the cohesion increased by 69.8% and 97.7%. Conclusion. Calcium-based nanomaterials fill in the pores between soil particles to support the soil particles, which greatly improves the mechanical strength and water stability of the specimen.